2019
DOI: 10.1038/s41467-019-08944-1
|View full text |Cite
|
Sign up to set email alerts
|

Atypical functional connectome hierarchy in autism

Abstract: One paradox of autism is the co-occurrence of deficits in sensory and higher-order socio-cognitive processing. Here, we examined whether these phenotypical patterns may relate to an overarching system-level imbalance—specifically a disruption in macroscale hierarchy affecting integration and segregation of unimodal and transmodal networks. Combining connectome gradient and stepwise connectivity analysis based on task-free functional magnetic resonance imaging (fMRI), we demonstrated atypical connectivity trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

41
433
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 392 publications
(522 citation statements)
references
References 75 publications
41
433
4
Order By: Relevance
“…Hence, although previous studies using SFC analysis tend to interpret their results in the sensory-to-cognitive direction (Carmona et al, 2015;Hong et al, 2019;Sepulcre et al, 2012), the directionality of the observed alterations should be tested in future studies using methods such as Dynamic Causal Modeling (Friston, Li, Daunizeau, & Stephan, 2011). First, computational constraints required us to downsample data to relatively large voxels (4 mm 3 ).…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, although previous studies using SFC analysis tend to interpret their results in the sensory-to-cognitive direction (Carmona et al, 2015;Hong et al, 2019;Sepulcre et al, 2012), the directionality of the observed alterations should be tested in future studies using methods such as Dynamic Causal Modeling (Friston, Li, Daunizeau, & Stephan, 2011). First, computational constraints required us to downsample data to relatively large voxels (4 mm 3 ).…”
Section: Limitationsmentioning
confidence: 99%
“…If SFC decrease was affecting sensory-to-cognitive functional streams, this would involve a reduced information feed from sensory up to higher level association nodes; if it was affecting cognitive-to-sensory functional streams, this would entail lower cognitive control over incoming perceptual information-thus hindering selective attention. Hence, although previous studies using SFC analysis tend to interpret their results in the sensory-to-cognitive direction (Carmona et al, 2015;Hong et al, 2019;Sepulcre et al, 2012), the directionality of the observed alterations should be tested in future studies using methods such as Dynamic Causal Modeling (Friston, Li, Daunizeau, & Stephan, 2011).…”
Section: Limitationsmentioning
confidence: 99%
“…In addition to leveraging surface-based processing and multimodal co-registration techniques, we harnessed a novel analysis reference frame determined by the putative neocortical hierarchy. Initially formulated in nonhuman primates (Mesulam, 1998), the hierarchy follows a "sensory-fugal" gradient from low-level cortices involved in interactions with the external world to higher-order transmodal areas involved in self-generated, abstract cognition (Buckner & Krienen, 2013;Huntenburg, Bazin, & Margulies, 2018;Margulies et al, 2016;Paquola et al, 2019;Hong et al, 2019). Recent application of unsupervised compression techniques applied to cortico-cortical functional connectivity data recapitulated a similar gradient in humans (Margulies et al, 2016).…”
Section: Introductionmentioning
confidence: 97%
“…During early-life development, a time when atypical development is often first diagnosed, rapid changes occur in connectome that is subject to the competing forces of module segregation for functional specialization, and inter-module integration to facilitate behaviors combining specializations (Homae et al, 2010). A reduction in this integration appears to be a key characteristic of autism (Abbott et al, 2016;Duan et al, 2017;Keown et al, 2013Keown et al, , 2017, and in particular the switching between local and global processing (Hong et al, 2019). By virtue of their long-range influence and ubiquity in the connectome, weak links are suggested as a potential substrate for integrative communication, and thus metrics sensitive to their distribution could be informative of neurodevelopmental disorders such as autism.…”
Section: Introductionmentioning
confidence: 99%